Study of Thematic Education on Narcissistic Phenomenon and Its Recovery Efforts through Tazkiyatun Nafs - Al Amin, Mohammad Fuad Al Amin (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2025)
This study aims to examine the phenomenon of narcissistic personality from the perspective of the Qur'an using a thematic exegesis (tafsir maudhū‘ī) approach. The focus is on identifying narcissistic traits as reflected in Qur’anic narratives, as well as exploring the Qur’an’s response to such deviant personalities. This qualitative-descriptive research employs a library research method, drawing on primary data from relevant Qur’anic verses interpreted through authoritative exegetical sources such as Tafsir al-Kabir by Fakhruddin al-Razi, Tafsir al-Manar by Muhammad Abduh and Rashid Rida, and Tafsir al-Wasith by Sayyid Tantawi. The findings reveal that narcissistic personality traits—as defined in modern psychology, including an exaggerated sense of self-importance, an excessive need for admiration, and a lack of empathy—are clearly exemplified in figures such as Iblis, Pharaoh, Qarun, and segments of the Children of Israel. The Qur’an strongly condemns such behaviors as they contradict the core values of tawhid (monotheism) and human dignity. As a spiritual remedy, the Qur’an offers the concept of tazkiyatun nafs (purification of the soul), which involves three stages: takhalli (removal of blameworthy traits), tahalli (adornment with virtuous morals), and tajalli (manifestation of divine awareness within the self). These findings indicate that the Qur’an not only diagnoses deviant personality traits but also provides a holistic path of psychological and spiritual healing. This study contributes to the development of thematic Qur’anic interpretation and opens new avenues for integrating Islamic knowledge with contemporary psychological thought.